Ectoparasitosis, a rare cause of severe iron deficiency anemia: A case report. (September 2021) - Batool, Nuzhat; Song, David; Reyes, Jonathan Vincent M.; Ahmad, Saad; Skulkidis, Arigirios; Almas, Talal; Khedro, Tarek; Brown, Maritza
Abstract: Pediculosis is a common condition caused by an infestation of head and body louse (ectoparasites) and remains a public health concern. Generally, infestation presents as pruritus in children and has a benign course, but there have been a handful of cases reported in the literature describing severe iron deficiency anemia (IDA) in high-risk groups such as children, history of psychiatric disorder including depression, and low socioeconomic status. Though an uncommonly encountered etiology of anemia, the aim of this case is to increase awareness of a rare cause of severe anemia from an ectoparasites affecting a high risk population, even in developed countries. Highlights: Pediculosis is a common condition caused by an infestation of head and body louse (ectoparasites). Infestation can be asymptomatic, or involve tingling sensations of the skin, irritability, insomnia, and pruritus. In severe cases of infestation, it can, on a rare occasion, manifest as severe iron deficiency anemia. The clinical course can vary from benign skin infestation to severe debilitating anemia, but with use of pediculicide and hygiene maintenance the condition can be easily eradicated.